PKM PENGENALAN PENGELOLAAN SDM SISWA SMK YPW KRAKATAU STEEL CILEGON: MEMBANGUN KOMPETENSI SOFT SKILLS TEAMWORK DAN TIME MANAGEMENT MENUJU DAYA SAING INDUSTRI - Ria Safitri; Awan Anhara; Pebrianti Pawestri (Indonesian Collaboration Journal of Community Services (ICJCS), 2026)
This Community Service Program was conducted at SMK YPWKS Cilegon with the aim of improving students’ understanding of personal human resource management, teamwork, and time management as essential soft skills required in the industrial world. The main problem identified among students was the low awareness of the importance of coordination, discipline, and collaboration in completing tasks, which often led to inefficiency in group-based learning activities. To address this issue, the program was implemented using an interactive and participatory approach, including interactive lectures, workshops, group discussions, and simulation-based learning through a building tower activity using simple materials such as straws and tape. The results of the activity showed a significant improvement in students’ awareness and understanding of teamwork dynamics, role distribution, communication, and time management. Students also experienced a shift in perspective, realizing that successful task completion is not only determined by individual ability but also by effective team coordination. This program successfully bridged the gap between theoretical learning in school and the practical demands of the industrial world. Therefore, simulation-based learning combined with soft skills training is considered an effective method to enhance vocational students’ readiness for future workforce challenges.